CircC6orf132 Facilitates Proliferation, Migration, Invasion, and Glycolysis of Gastric Cancer Cells Under Hypoxia by Acting on the miR-873-5p/PRKAA1 Axis - Chen, Weizhi; Ji, Yanhong (Frontiers in Genetics, 2021)
Background: Hypoxia is a crucial factor in the progression of various tumors, including gastric cancer (GC). Circular RNAs (circRNAs) are important regulators in GC, and this study focused on researching circC6orf132 in GC progression under hypoxia. Methods: In vitro experiments were performed in GC cells under hypoxia (1% O2). CircC6orf132, microRNA-873-5p (miR-873-5p) and protein kinase AMP-activated alpha 1 catalytic subunit (PRKAA1) levels were examined by real-time polymerase chain reaction (qRT-PCR). Colony formation assay and transwell assay were used for detecting cell proliferation and migration or invasion. Glycolytic metabolism was evaluated using lactate production, glucose uptake and adenosine triphosphate (ATP) level and extracellular acidification rate (ECAR). Western blot was performed for determining protein expression. The target interaction was analyzed by dual-luciferase reporter and RNA immunoprecipitation (RIP) assays. In vivo assay was conducted via mice xenograft model. Results: The expression of circC6orf132 was signally high in GC cells under hypoxia. Hypoxia-induced GC proliferation, migration, invasion and glycolysis were reversed by silencing circC6orf132. CircC6orf132 targeted miR-873-5p and the inhibition of circC6orf132 knockdown for the effects of hypoxia on GC cells was abrogated by miR-873-5p inhibitor. PRKAA1 was validated as a downstream gene of miR-873-5p and miR-873-5p functioned as an anti-cancer molecule in GC cells under hypoxia by downregulating PRKAA1 level. CircC6orf132 could regulate PRKAA1 by sponging miR-873-5p. CircC6orf132/miR-873-5p/PRKAA1 axis could regulate GC progression under the hypoxic condition. CircC6orf132 downregulation reduced tumorigenesis in vivo through affecting the miR-873-5p/PRKAA1 axis. Conclusion: CircC6orf132 has been affirmed to promote proliferation, migration, invasion and glycolysis in GC under hypoxia, partly by depending on the regulation of miR-873-5p/PRKAA1 axis.